Uji Potensiasi Efek Sedatif – Hipnotik Ekstrak Etanol Biji Pinang (Areca Catechu L) Asal Papua Barat Daya terhadap Mencit Jantan: Mus Musculus - Arif Radhika Mentari; Lukman Hardia; Ratih Arum Astuti (STIKes Ibnu Sina Ajibarang, 2025)
Sleep is a vital state of rest for humans to maintain a healthy body. After a day of activity, the body requires adequate sleep to recover and regain energy. One common sleep disorder is insomnia, characterized by difficulty sleeping both in terms of quality and quantity. Insomnia has traditionally been treated with sedatives, drugs that reduce anxiety and provide a calming effect with little or no impairment to motor and mental function. However, long-term use of chemical drugs can cause side effects, necessitating alternatives, one of which is the use of traditional medicine. Areca nut (Areca catechu L.) is known to possess antioxidant, antimutagenic, astringent (tightening), and intoxicating properties that have long been used in traditional medicine. This study was conducted experimentally in a laboratory to determine the sedative-hypnotic effects of areca nut ethanol extract. The observed parameter was survival time on the rotarod, and the data were analyzed using one-way ANOVA for homogeneity testing and Shapiro-Wilk for normality testing. If the data were not homogeneous or normal (p < 0.05), the analysis was continued with the nonparametric Kruskal-Wallis and Mann-Whitney tests. The results showed that administration of areca nut ethanol suspension as a positive control with varying doses did not produce significant differences, meaning that all three doses had the same sedative-hypnotic effect. In the treatment groups with areca nut ethanol extract doses of 0.52 mg/kgBW and 0.78 mg/kgBW, significant differences were observed compared to the negative control, indicating a clear sedative-hypnotic effect. Therefore, it can be concluded that areca nut (Areca catechu L.) ethanol extract at doses of 0.52 mg/kgBW and 0.78 mg/kgBW has the potential to provide sedative-hypnotic effects and can therefore be used as an alternative treatment for sleep disorders.